Critical Path Method (CPM) pada pengerjaan pipeline dan analisis resiko pada pengelasan - Febriti Aryan Kumala; Endang Pudji Purwanti; Mochammad Karim Al Amin (Politeknik Negeri Lhokseumawe, 2021)
The pipeline construction project at PT. Gearindo Prakarsa often delays because many activities are not in accordance with the target, this is due to the repair process on welding and lack of manpower in some activities. This results in the actual duration being longer than the planning duration. So it is necessary to control the control through optimizing the schedule and implementation costs as well as risk analysis for the welding process. CPM and crashing methods are one of the methods used in controlling to get a more optimal time and cost duration. Meanwhile, to overcome any improvements made by conducting a risk analysis to determine the risk of defects from safety, environmental and cost factors. If the welding activity does not change the welding process, using the CPM and crashing methods, the optimal time is 59 days by adding 15 workers and costs Rp. 9,001,453. If the overall welding process changes with SMAW or GTAW, by analyzing the increase in consumption costs of Rp. 27,72,000 for the SMAW process and Rp. 44,366,169, for the GTAW process. In terms of the level of risk, porosity defects and incomplete fusion in the SMAW process are at a high risk level for safety, environmental and cost factors. Meanwhile, in the GTAW process, complete fusion defects are at a high risk level for the cost factor.